2005
DOI: 10.14411/fp.2005.049
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hemolivia mauritanica (Apicomplexa: Adeleina: Haemogregarinidae) in natural populations of tortoises of the genus Testudo in the east Mediterranean region

Abstract: Abstract. Hemolivia mauritanica (Sergent et Sergent, 1904) infections were found in 14% (n = 14) of Testudo graeca Linnaeus, 1758 tortoises in Bulgaria and in 92% (n = 26) of those in Turkey. Hemolivia mauritanica-like gametocytes were found in 81% (n = 47) of wild Testudo marginata Schoepff, 1792 tortoises in Greece. Parasitaemia intensity (the percentage of infected red blood cells found in approximately 10 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…More prominent differences may be observed in geographical distribution and in molecular features of Hemolivia species. Parasites from chelonian hosts were recorded in Vietnam ( H. cruciata ), Mozambique ( H. parvula ), and in the Mediterranean and Middle East ( H. mauritanica ) [ 3 , 6 , 22 , 24 , 31 ]. There is one more report of Hemolivia in Rhinoclemmys turtle: Nordmeyer et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More prominent differences may be observed in geographical distribution and in molecular features of Hemolivia species. Parasites from chelonian hosts were recorded in Vietnam ( H. cruciata ), Mozambique ( H. parvula ), and in the Mediterranean and Middle East ( H. mauritanica ) [ 3 , 6 , 22 , 24 , 31 ]. There is one more report of Hemolivia in Rhinoclemmys turtle: Nordmeyer et al .…”
Section: Resultsmentioning
confidence: 99%
“…Hemolivia mariae Smallridge et Paperna, 1997 is a species infecting Australian skinks Tiliqua rugosa and Egernia stokesii [26,27]. Three species of Hemolivia have been described from chelonian hosts: Hemolivia mauritanica (Sergent et Sergent, 1904) infecting Palearctic tortoises Testudo graeca and T. marginata [1,13,17,[20][21][22], Hemolivia parvula (Dias, 1953) from the African tortoises Kinixys zombensis and Stigmochelys pardalis [3], and Hemolivia cruciata Zechmeisterová et Široký, 2022 infecting Vietnamese box turtle Cuora galbinifrons [31]. Hemolivia argantis (Garnham, 1954) originating from Egypt was first described as Hepatozoon argantis from the soft tick Argas brumpti.…”
Section: Introductionmentioning
confidence: 99%
“…Infection present in the northern Golan Heights (Masáda) and is apparently absent further south, in the Golan Heights around Lake Kinneret (Kanaf) as well as further south in Israel and Palestine. The northern Golan Heights with its higher altitude (~1,000 m), lush vegetation (oak forest at the site of collection), lower temperatures (~0º in winter) and heavier precipitation (~1,000 mm annually) is more comparable to the northern Mediterranean environment from which many of the infection in tortoises have been reported ( Siroký et al, 2005). The more southern habitats (of ~600 m altitude) are more arid (~400 mm precipitation annually) with sparser and lower vegetation (Climate in Israel: http://www.tapuz.co.il).…”
Section: Discussionmentioning
confidence: 99%
“…Brumpt (1938) demonstrated that the sporogonous stages seen by Laveran & Negre (1905) in the tortoise tick Hyalomma aegyptium L. are infective by ingestion to T. graeca. Recently, new records have been published on the distribution of H. mauritanica infections among T. graeca in Bulgaria and Turkey, and T. marginata in Greece, while T. hermanni from Bulgaria, Greece and Croatia were found negative ( Siroký et al, 2005); both tortoise species were infested with Hy. aegyptium, and sporocysts were recovered from ticks removed from both hosts ( Siroký et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation